2018
DOI: 10.1111/desc.12774
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging children to mentalise about a perceived outgroup increases prosocial behaviour towards outgroup members

Abstract: We investigated whether encouraging young children to discuss the mental states of an immigrant group would elicit more prosocial behaviour towards them and impact on their perception of a group member's emotional experience. Five‐ and 6‐year‐old children were either prompted to talk about the thoughts and feelings of this social group or to talk about their actions. Across two studies, we found that this manipulation increased the extent to which children shared with a novel member of the immigrant group who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…In contrast, prosocial modalities that require empathetic responding and mental state attribution may show greater sensitivity to in‐group bias (Over, 2018). For instance, children are more like to attribute mental states to in‐group members and show greater prosociality when they are encouraged to attribute mental states to out‐group members (McLoughlin & Over, 2017, 2019). Thus, future research examining the influence of gender bias across prosocial domains will provide important insight into how and when gender bias influences prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, prosocial modalities that require empathetic responding and mental state attribution may show greater sensitivity to in‐group bias (Over, 2018). For instance, children are more like to attribute mental states to in‐group members and show greater prosociality when they are encouraged to attribute mental states to out‐group members (McLoughlin & Over, 2017, 2019). Thus, future research examining the influence of gender bias across prosocial domains will provide important insight into how and when gender bias influences prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This effect held across two different types of group division—those based on gender and nationality. It remains for future research to determine whether hearing language of this sort influences children's attitudes and behaviour (McLoughlin & Over, ).…”
Section: Conceptualising the Social Learning Processmentioning
confidence: 99%
“…Beyond this, research-led interventions may offer promising routes for tackling the effects of dehumanization before they become deeply entrenched later in development (Dunham & Degner, 2010). In a recent effort, McLoughlin and Over (2017b) found that 5-and 6-year-olds who were encouraged to mentalize about an immigrant group were more helpful toward a novel victim belonging to that group. Mental state attribution is only one aspect of this complex social phenomenon (Smith, 2012); therefore, future research is required to explore whether reinforcing the humanity of vulnerable social groups in other ways is successful in alleviating the negative, and often detrimental, outcomes of dehumanization in young children (e.g., see Albarello & Rubini, 2012;Bruneau, Cikara, & Saxe, 2015;Vezzali, Capozza, Stathi, & Giovannini, 2012).…”
Section: Questions For Future Researchmentioning
confidence: 99%